Investigation of Sn(IV) and Sn(II) by dianionicligand compounds Supported by Nitrogen-Based Ligands - Shannon Khalaf, Majid (Iraqi Journal of Science, 2023)
Synthetic routes to a series of tin compounds incorporating nitrogen-basedchelating ligands are described. The β-diketiminato tin chloride precursor wasutilized to isolate the first tin-phosphorus tin compound using this ligand,[(HC{C(Me)NAr}2)SnPPh2]. A diamide ligand was employed to investigate tin (II)and (IV) compounds. Two tin (II) and (IV) compounds, [(Me2Si{ArN}2)SnPh2] and[Li(OEt)2](Me2Si{ArN}2)SnPh2], were formed via reaction of the lithiatedpreligand, [Me2Si{ArNLi}2]+Sn(IV). Finally a novel Sn(II) N-heterocyclicstannylene compound was formed by reaction of the preligand with SnCl4.The diamide ligand was found to be suitable for both Sn(IV) and Sn(II)compounds. Reaction to obtain the tin dichloride compound resulted in theformation of [Li(OEt2)2][LSnCl3], which was characterised to be the chloro-bridgedlithium chloride adduct of the desired compound. To gain more information on thisreaction it was repeated with SnCl2Ph2 to attain the tin diphenyl analogue, whichwas established with no problems. Reaction to generate a N-heterocylic stannylenewas extremely interesting, as this compound has great potential for further reactivityboth independently and with regards to the aim of this product, which was togenerate a tin-phosphorus multiple bond.